Strategi Peningkatan Layanan dengan Aplikasi Simpadu untuk Efisiensi Operasional Kapal di Pelabuhan Kelas II Benoa - Anandita Susatya, Renissa Velda; Amrullah, Romanda Annas; Gupron, Akhmad Kasan (Innovative: Journal Of Social Science Research, 2025)
This study aims to find strategies to improve the simpadu aplication for vessel operational that are suitable for implementation at Port Authority Class II Benoa. The type of research is qualitative, so the sources and data collection used consist of narratives from observations, documents, and interviews conducted by the researcher with the informants. As for the data analysis, it employs qualitative descriptive analysis, which aims to draw conclusions from data gathered from observations, interviews, and documentation, followed by data standardization and extracting relevant information for the research